DOES ESG PERFORMANCE REDUCE FINANCIAL DISTRESS? THE MEDIATING ROLE OF FIRM VALUE - Muhammad Pondrinal; Rahmat Wahyudi; Dodi Suryadi; Yosi Puspita Sari (JAT : Journal Of Accounting and Tax, 2026)
This study examines the effect of ESG performance on financial distress with firm value as a mediating variable among non-financial companies included in the LQ45 Index during the 2021–2025 period. The study employs a quantitative research approach using panel data regression analysis. The sample consists of 16 non-financial companies selected through purposive sampling, resulting in 80 balanced panel observations. ESG performance is measured using ESG scores obtained from Refinitiv Eikon, financial distress is measured using the Ohlson O-Score model, and firm value is proxied by Tobin’s Q. The analysis includes the Common Effect Model (CEM) and mediation analysis using the Sobel test. The findings indicate that ESG performance does not significantly affect financial distress or firm value. In addition, firm value is unable to significantly influence financial distress and does not mediate the relationship between ESG performance and financial distress. Meanwhile, firm size negatively affects financial distress, whereas leverage positively affects financial distress. These findings suggest that ESG implementation among LQ45 companies has not yet been fully translated into stronger market valuation and improved financial resilience. This study contributes to the sustainable finance literature by providing empirical evidence regarding the limited role of ESG performance in reducing financial distress in emerging market contexts. The findings also provide practical implications for managers, investors, and policymakers in strengthening the effectiveness of sustainability practices and long-term corporate financial stability.